Factors Associated with Poor Sleep Quality in Postpartum Women: A Crossectional Study - Ana Júlia Pereira Motta; Roselma Lucchese; Graciele Cristina Silva Leão; Dayane Eusenia Rosa; Vilmar De Assis Gonçalves; Revora Silverio Mendonça (Sleep Science)
Objective This study aimed to analyze the factors associated with poor sleep quality in women in the postpartum period who were assisted in a municipality in central Brazil.